2013
DOI: 10.1007/s10653-013-9540-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis as a tool to investigate the bioaccessibility of nickel, vanadium and zinc in Northern Ireland soils

Abstract: Correlation analyses were conducted on nickel (Ni), vanadium (V) and zinc (Zn) oral bioaccessible fractions (BAFs) and selected geochemistry parameters to identify specific controls exerted over trace element bioaccessibility. BAFs were determined by previous research using the Unified BARGE Method. Total trace element concentrations and soil geochemical parameters were analysed as part of the Geological Survey of Northern Ireland Tellus Project. Correlation analysis included Ni, V and Zn BAFs against their to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Using generic bedrock types ensures that sample sizes remain sufficiently robust during analysis and EDA, as defining discrete minor geologic formations present in Northern Ireland would reduce sample sizes to a prohibitively narrow range of statistical significance. Such an approach also reduces variance and increases normality in the distribution of geochemistry data (Jordan et al, 2007;Zhang et al, 2007;Palmer et al, 2013).…”
Section: Study Area and Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using generic bedrock types ensures that sample sizes remain sufficiently robust during analysis and EDA, as defining discrete minor geologic formations present in Northern Ireland would reduce sample sizes to a prohibitively narrow range of statistical significance. Such an approach also reduces variance and increases normality in the distribution of geochemistry data (Jordan et al, 2007;Zhang et al, 2007;Palmer et al, 2013).…”
Section: Study Area and Sample Selectionmentioning
confidence: 99%
“…Previous trace element bioaccessibility research in Northern Ireland has shown that oral bioaccessibility is not primarily a function of total trace element concentrations in soil (Barsby et al, 2012;Palmer et al, 2013;Cox et al, 2013), diminishing the suitability of reliance on total soil contaminant concentrations as a driver for contaminated land management decisions. Following from these findings, specific geochemical factors accounting for the variability in trace element bioaccessibility across the country ϯ require further investigation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…represented across Northern Ireland (Barsby et al 2012;Palmer, et al 2013). The method used for assessing the bioaccessibility of soil samples was the Unified BARGE Method (Wragg et al 2009;BARGE -INERIS, 2011).…”
Section: Bioaccessibilitymentioning
confidence: 99%
“…The method represented the oral exposure pathway through the stomach, and stomach with intestine using synthetic materials in place of the digestive system including gastric fluid, saliva, duodenal fluid and bile (Barsby, et al 2012). This research used the bioaccessible fraction (BAF %) analysed by Barsby et al (2012) and Palmer, et al (2013) which was calculated from the Unified BARGE Method test for each sample using the highest bioaccessible PTE concentration of the digestive extracts. Full details of the Unified BARGE Method used to produce the BAF data used in this study are provided in Barsby et al (2012).…”
Section: Bioaccessibilitymentioning
confidence: 99%